Rigor With or Without Templates? The Pursuit of Methodological Rigor in Qualitative Research. (April 2022) - Harley, Bill; Cornelissen, Joep
The domain of qualitative research is replete with templates, standard protocols for the analysis of qualitative data. The use of such templates has sometimes been considered as automatically enhancing the rigor of qualitative research. In this article, we challenge the view that in the context of qualitative research, rigor is tied into the application of established protocols. Instead, we argue that rigor emanates from the way in which researchers engage in a deliberate reasoning process of inferring theoretical claims from their data. Such reasoning exists outside of templates, although it may make use of templates. Framing rigor as an emergent quality of reasoning, we distill the main processes through which qualitative researchers derive inferences from data and provide criteria for reflecting on the rigor with which they do so. We then extend these criteria into a set of practical recommendations through the presentation of examples and the framing of questions to focus researchers' thinking on the application of the criteria. In doing so, we aim to help qualitative researchers to conduct research that leads to rigorously derived theoretical insights without having to resort to templates to attempt to do so.